Desarrollo de una aplicación móvil, para S.O android, que automatice el levantamineto de la información del inventario para la zona 9 (Pichincha) del MSP - Cueva Coronado, Natalia Pamela (2017)
Smart mobile devices known as smart devices have become an indispensable work tool, so you can make and receive calls, have a connection for permanent communication, and install applications useful to carry out daily tasks among other functionalities. At present, most of the devices available in the market have the Android operating system because it is a free access platform. After a brief introduction of the features and tools of this platform, an application will be analyzed, designed and developed for the collection of information from the inventory of the family file of the Ministry of Public Health. The main function of this application is the entry of family files, in addition to connecting with a server to store the information and allow the download of the tabs for the annual monitoring carried out by the institution. This application will contain mostly drop-down lists for data recording and the minimum entry of these fields manually will allow to avoid delays, incompatibilities, losses and little readability in the delivery of information becoming a fundamental instrument to establish the conditions of Health of the population of the area, their needs, the economic and social environment, health problems of the family group to make decisions for the community.